The Relationship Between Prior Knowledge and EFL Learners' Listening Comprehension: Cultural Knowledge in Focus - Samian, Samira Hayati; Dastjerdi, Hossein Vahid (Mediterranean Journal of Social Sciences, 2012)
The present study investigated the impact of cultural familiarity on improving Iranian EFL learners’ listeningcomprehension. To do this, forty English language learners were selected at a private language institute in Isfahan based ontheir scores in FCE test and were randomly assigned to four groups of ten. A pre-test was administered to the four groups beforeany treatment. During the experiment, Group A had exposure to target culture texts. The participants in Group B had exposure tointernational target culture texts. The participants in Group C had exposure to source culture texts. The participants in Group Dhad only exposure to culture free texts. At the end of this treatment, the four groups took a post-test which was the same as pretestto see whether the treatment had any influence on their listening proficiency. The results of the post-test showed that thefour groups performed differently on the post-test, which indicated that greater familiarity with specific culturally-orientedlanguage listening material would improve Iranian EFL learners’ listening proficiency.